Optimizing PAPR performance for 6G OTFS waveform using adaptive genetic PTS method for Rician fading channels - Arun Kumar; Aziz Nanthaamornphong; Nishant Gaur (EURASIP Journal on Advances in Signal Processing)
Abstract This paper proposes a novel method for reducing the peak-to-average power ratio (PAPR) in orthogonal time–frequency space (OTFS) modulation over Rician fading channels using an adaptive genetic algorithm-based partial transmit sequence (AGA-PTS) technique. The PAPR is a significant challenge in multicarrier systems, often leading to nonlinear distortions. The proposed AGA-PTS method enhances conventional genetic algorithms by adaptively tuning the crossover and mutation rates according to the convergence behavior, leading to improved optimization efficiency and reduced signal distortion. By minimizing the phase shifts of each subblock, the AGA-PTS achieves substantial PAPR reduction while preserving the signal integrity. Compared to traditional methods, such as standard partial transmit sequence (PTS), selective mapping, and companding, AGA-PTS offers faster convergence and lower computational complexity owing to its dynamic phase adaptation mechanism. Simulation results demonstrate PAPR reductions of 2.2–4 dB and SNR improvements of 1.9–4.8 dB at a BER of 10⁻4. Further, power spectral density analysis shows that the proposed method gives −995 Watt per Hertz, resulting in efficient spectrum use, and thus, it is promising for OTFS modulation in real-world wireless systems.